Is There any Scope for Corporatism in Stabilization Policies? - Giovanni Di Bartolomeo; Nicola Acocella; Wilfried Pauwels (Fondazione Eni Enrico Mattei (FEEM), 2004)
This paper studies corporatism as the outcome of bargaining between the government and a representative labor union. When negotiations between these two parties only relate to macroeconomic stabilization, we show that corporatism can never be beneficial to both parties. As corporatist policies are nevertheless commonly observed in this context, we also discuss in an informal way possible explanations that reconcile the theory with actual observations. The policy implications of these explanations are also discussed.
Keywords: E00; E58; E61; J50; 330; Social pacts; Axiomatic bargaining; Unions; Issue linkage; Einkommenspolitik; Konjunkturpolitik; Sozialpakt; Korporatismus; Spieltheorie